2003
DOI: 10.1159/000072429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Partial-Length Genomic Segment 2 of Human Picobirnavirus

Abstract: Objectives: This study was carried out in order to evaluate the efficacy of the recently developed picobirnavirus (PBV) sets of primers and to establish the phylogenetic relationships of Argentine strains with PBV strains isolated in China and the USA. Methods: Thirteen fecal specimens tested as positive for PBV by polyacrylamide gel electrophoresis were analyzed by reverse transcription-polymerase chain reaction assays using primers target to the genomic segments 2 of PBV strains isolated in China and the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
33
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
5
33
0
Order By: Relevance
“…The deduced amino acid sequences showed that all the clones encoded the conserved residues D-S-D and clone PBV2-POR encoded additionally the conserved residues SG-T-E, corresponding, respectively, to motifs 1 and 2 of the RNA-dependent RNA polymerases of dsRNA viruses (6), thus confirming previous results obtained with human PBV which postulated that genomic segment 2 encodes the polymerase of these viruses (23,27,29).…”
supporting
confidence: 84%
See 4 more Smart Citations
“…The deduced amino acid sequences showed that all the clones encoded the conserved residues D-S-D and clone PBV2-POR encoded additionally the conserved residues SG-T-E, corresponding, respectively, to motifs 1 and 2 of the RNA-dependent RNA polymerases of dsRNA viruses (6), thus confirming previous results obtained with human PBV which postulated that genomic segment 2 encodes the polymerase of these viruses (23,27,29).…”
supporting
confidence: 84%
“…The larger RNA segment, or segment 1, contains two open reading frames encoding 224 and 552 amino acids, while the small RNA segment, or segment 2, contains a single open reading frame encoding 534 amino acids (29). The small segment encodes amino acid motifs typical of those encoded by the RNA-dependent RNA polymerase genes (23,27,29). Because of its genomic and morphological characteristics, this novel group of viruses is a likely candidate for a new taxon.…”
mentioning
confidence: 99%
See 3 more Smart Citations